2005
DOI: 10.1161/circulationaha.104.479295
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mechanisms Underlying the Development of Catecholaminergic Ventricular Tachycardia

Abstract: Background-Mutations in the ryanodine 2 receptor (RyR2) gene have been identified in patients with catecholaminergic polymorphic ventricular tachycardia. We examined the cellular basis for the ECG features and arrhythmia mechanisms using low-dose caffeine to mimic the defective calcium homeostasis encountered under these conditions. Methods and Results-A transmural ECG and action potentials were recorded simultaneously from epicardial, M, and endocardial cells in arterially perfused canine ventricular wedge pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 31 publications
2
62
0
Order By: Relevance
“…The altered regional properties of cardiac tissue may have affected locally the refractoriness of the myocardium, negatively interfering with electrical conduction and pattern of impulse propagation. Although further experiments are warranted, these initial findings suggests that altered spatial heterogeneity of the myocardium with diabetes represents the basis for the alternation in the polarity of the QRS axis observed during episodes of BVT 29, 58…”
Section: Discussionmentioning
confidence: 96%
“…The altered regional properties of cardiac tissue may have affected locally the refractoriness of the myocardium, negatively interfering with electrical conduction and pattern of impulse propagation. Although further experiments are warranted, these initial findings suggests that altered spatial heterogeneity of the myocardium with diabetes represents the basis for the alternation in the polarity of the QRS axis observed during episodes of BVT 29, 58…”
Section: Discussionmentioning
confidence: 96%
“…A similar protocol was repeated after switching the basic stimulus (S 1 ) to epicardium as reversal of direction of activation of the left ventricle has been shown to amplify TDR and facilitate induction of pVT. 15 The effective refractory period (ERP) was defined as the longest S 1 -S 2 interval at which S 2 failed to capture. Ventricular tachycardia (VT) inducibility was examined under each condition (control, PD-118057, + Quinidine).…”
Section: Methodsmentioning
confidence: 99%
“…Work on ventricular wedge preparations found that increasing RyR probability (with caffeine) did not produce arrhythmias unless catecholaminergic stimulation was also present. 17 This study, however, did not investigate cellular Ca 2ϩ handling.…”
mentioning
confidence: 95%